2020
DOI: 10.2174/1574893614666190722165130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Germin-like Protein Genes (OsGLPs) Family in Rice Using Various In silico Approaches

Abstract: Background: Germin-like Proteins (GLPs) play an important role in various stresses. Rice contains 43 GLPs, among which many remain functionally unexplored. The computational analysis will provide significant insight into their function. Objective: To find various structural properties, functional importance, phylogeny and expression pattern of all OsGLPs using various bioinformatics tools. Methods: Physiochemical properties, sub-cellular localization, domain composition, Nglycosylation and Phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 76 publications
10
21
0
Order By: Relevance
“…Considering the functional characterization and expression analysis of GLP genes in rice, previous studies have mainly focused on Oryza Sativa Japonica as compared to other sub-species (Indica and Javanica) of rice crop [9,20,21]. Moreover, not many studies have compared the genomic responses of OsGLP genes across tolerant and sensitive rice varieties under abiotic stresses mainly including salt and drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the functional characterization and expression analysis of GLP genes in rice, previous studies have mainly focused on Oryza Sativa Japonica as compared to other sub-species (Indica and Javanica) of rice crop [9,20,21]. Moreover, not many studies have compared the genomic responses of OsGLP genes across tolerant and sensitive rice varieties under abiotic stresses mainly including salt and drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…In silico assessment in Japonica rice cultivar suggested that OsGLP genes from chromosome 3 and 8 are functionally more linked as compared to other OsGLPs by regulating in a combinatorial manner to deal with various abiotic stress conditions. [21]. Although such studies indicated the salt and drought stress responsive nature of OsGLPs, however, not many reports are available on the comparative expression analysis of OsGLPs in multiple rice varieties under these stresses.…”
Section: Introductionmentioning
confidence: 99%
“…We used four metrics to quantify the predictive results [37, 40, 51–74] and thereby evaluate the proposed method.…”
Section: Methodsmentioning
confidence: 99%
“…We use sensitivity (SN), specificity (SP), accuracy (ACC), Matthews correlation coefficient (MCC) to measure the quality of the classifier for DS1 and DS2 (Amanat et al, 2020;Chen et al, 2020;Ikram et al, 2020;Ilyas et al, 2020;Kong et al, 2020;Liang and Zhang, 2020;Lv et al, 2020bLv et al, , 2021b. The calculation formula is as formula (3).…”
Section: Performance Evaluationmentioning
confidence: 99%